Peace Guidance, Applied Study of Character Improvement of Pancasila Student Profile through Integrated Guidance and Counseling Services: ENG - Gusman Lesmana; Sri Ngayomi Yudha Wastuti; Deliati (Department of Guidance and Counseling, FIP, Undiksha, 2025)
The problem of low student character in terms of honesty, responsibility, discipline, and empathy is a major challenge in today's education world. This condition shows the need for a more humanistic and transformative approach in guidance and counseling services. This study aims to examine the effectiveness of the implementation of peace guidance in improving student character based on the dimensions of the Pancasila Student Profile. The type of research used is a quasi-experimental study with a pretest-posttest control group design. The subjects of the study consisted of 552 students, who were randomly divided into experimental and control groups. Data were collected through a student character questionnaire based on the Pancasila Student Profile, observation, and structured interviews. The questionnaire instrument has been tested for validity and reliability before being used. The data analysis technique used is path analysis to determine the relationship between peace guidance and strengthening student character in each dimension of the Pancasila Student Profile. The results of the study indicate that peace guidance makes a significant contribution to improving student character, with a correlation coefficient value for the dimensions of faith and piety of 1.00; mutual cooperation 0.656; independence 0.905; critical reasoning 0.920; and creativity 0.208. Techniques applied in the service include reflective dialogue and role-playing which have proven effective in fostering empathy, self-awareness, and conflict resolution skills. The conclusion of this study is that the integration of peace values in guidance and counseling services is consistently able to strengthen students' character according to the six dimensions of the Pancasila Student Profile.